Analysis of the Probability of Successful Completion Time of the Penganten-Ngampal Road Reconstruction Project Using the PERT Method - Al-Putro, Akmal Puguh; Nugroho, Laksono Djoko; Muhammadun, Haris (INTERNATIONAL JOURNAL ON ADVANCED TECHNOLOGY, ENGINEERING, AND INFORMATION SYSTEM, 2025)
Infrastructure project delays are often a major challenge in the construction industry, including the Penganten - Ngampal Road Reconstruction project which experienced a 50-day delay from the initial target. This problem is caused by the uncertainty of external factors such as weather and limited resources. This research aims to calculate the probability of success of project completion time using quantitative descriptive method with Program Evaluation and Review Technique (PERT) approach. This method involves three estimates, namely optimistic, most likely, and pessimistic times to evaluate the average duration and critical path of the project. The data used consisted of project reports, field observations, and calculations using POM-QM software. The analysis shows that the project critical path consists of activities A, C, D, E, and F with a total duration of 60 days. The probability of completing the project within 60 days reached 98.21%, showing the effectiveness of the PERT method in managing time uncertainty.